Impact Of COVID-19 On Patients Requiring Spine Surgery: A Tertiary Level Government Trauma Hospital Experience - Dhakal, Gaurav Raj; Shrestha, Sushil; Shah, Gyanendra (Journal of Nepal Health Research Council, 2022)
Background: The COVID-19 outbreak caused by the SARS Corona virus 2 (SARS-CoV-2), that appeared in Wuhan, China in December 2019 evolved into a pandemic and caused a devastating effect in all aspect of life. The aim of this study is to determine the impact of Covid-19 on the management of spine patients requiring surgery and to observe the functioning of a trauma center in a pandemic situation. Methods: A retrospective study was performed at National Trauma Center, Kathmandu, Nepal from January 1 2019 to February 28 2020(Pre-Covid period) and March 1 2020 to April 30 2021(Covid Period) . All patients undergoing spine surgery were included and details regarding demographics, diagnosis, surgical procedures were obtained and compared between pre- covid and covid period and also between complete lockdown period and partial lockdown period of the covid duration. Results: The mean age of the patients undergoing surgery in the Pre covid period was (40.4 ± 14.51) years and covid period was (38.9 ± 14.00) years. The number of spine surgeries performed during the pre covid period was 295 whereas the number decreased to 197 in the covid period. The total number of non traumatic spine surgery in the pre covid period was 22.03% of the total spine surgery cases where as it decreased to 11.68% in the covid period. Similarly out of the total cases instrumented surgery was 91.86% in the pre covid period whereas it was 97.97% in the covid period. While analyzing the spine surgery done in the COVID period we found that most of the cases of surgery done in the complete restriction period was of traumatic spine only (97.77%) where as in the limited restriction period non traumatic spine surgery was also increased with traumatic spine surgery accounting for 85.52% of the total spine surgery cases. Conclusions: The COVID pandemic has had a direct impact on traumatic and non-traumatic spine surgeries performed in this center. Keywords: COVID-19; government tertiary hospital; spine surgery